2018
DOI: 10.1096/fj.201700783rr
|View full text |Cite
|
Sign up to set email alerts
|

Excess maternal fructose consumption impairs hippocampal function in offspring via epigenetic modification of BDNF promoter

Abstract: Recent increases in fructose consumption have raised concerns about the potential adverse intergenerational effects of excess fructose intake. In the present study, we investigated whether excess maternal fructose intake affects hippocampal function in offspring. Female Sprague-Dawley rats were divided into 3 experimental groups: one group received distilled water, one group received 20% fructose water, and one group received 20% glucose water in addition to standard chow during gestation and lactation. Hippoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
37
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 48 publications
9
37
0
2
Order By: Relevance
“…In agreement with our previous study, our present results suggest that maternal fructose-induced alterations to hippocampal Tfam and Ucp5 expression could be mediated by changes in epigenetic modifications (17). Specifically, maternal fructose intake led to the increased DNA methylation of a putative SP1 binding sequence in the gene promoter, resulting in the suppression of its transcription.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In agreement with our previous study, our present results suggest that maternal fructose-induced alterations to hippocampal Tfam and Ucp5 expression could be mediated by changes in epigenetic modifications (17). Specifically, maternal fructose intake led to the increased DNA methylation of a putative SP1 binding sequence in the gene promoter, resulting in the suppression of its transcription.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, it was found to up-regulate the methylation of hepatic peroxisome proliferator-activated receptor a and carnitine palmitoyltransferase 1A promoters and decrease the methylation of mtDNA in adult rats (4,5). It should be noted that the transgenerational epigenetic effects of fructose occurred in offspring (17,28). Similar to our previous results, current findings showed that DNA methylation is highly sensitive to high fructose consumption.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations